Decider - Francis, Dick, 1920-2010 1920-2010 (Michael Joseph, 1993)
Architect Lee Morris inherits a partial ownership in the Stratton Park racecourse--and with it, a dangerous position among the warring upper-class family trying to settle its fate.Morris would like to see the course restored to its former grandeur, but the various Stratton heirs have plans of their own.When an explosion rocks the grandstands, the disagreement turns violent--and Morris finds himself in a race to save himself and his family from an unknown culprit...